Risk factors for postpartum psychiatric disorders: A systematic review - Sitawati, Andini Dyah; Fahma, Hilmia; La Tabari, Muhammad Fadhlan; Ratnaningsih, Tri; Antariksa, Putri Mayang Sari; Agustiawan, Agustiawan (Institute of Computer Science (IOCS), 2025)
Introduction: Postpartum psychiatric disorders, particularly postpartum depression, are one of the most common psychological complications affecting maternal and neonatal well-being. These conditions are often underdiagnosed and undertreated, particularly in developing countries. Identifying risk factors is crucial for prevention and early detection. Objective: This systematic review aims to identify and analyze risk factors contributing to postpartum psychiatric disorders based on scientific evidence from 2015 to 2025. Methods: A literature search was conducted through PubMed, Scopus, ScienceDirect, and Web of Science databases using the keywords “postpartum depression,” “psychiatric disorder,” and “risk factors.” Included articles were observational human studies, written in English or Indonesian, reporting risk factors and postpartum psychiatric outcomes. Of the 1,026 articles screened, nine studies met the inclusion criteria. Results: The most consistent risk factors found included a history of previous psychiatric disorders, low social support, perinatal stress, low economic status, obstetric complications, and postpartum immunological dysregulation. Eight of the nine studies showed a significant association (p < 0.05). Conclusion: Postpartum psychiatric disorders are multifactorial, influenced by biological, psychological, and social factors. Preventive efforts should focus on antenatal screening, strengthening social support, and monitoring the mother's mental state after delivery.